Intervenções terapêuticas nutricionais nos pacientes com transtorno de compulsão alimentar periódica grave - Minari, Tatiana Palotta (2019)
The binge eating disorder (BED) is a psychiatric illness related to the frequency of binge eating episodes, body image dissatisfaction, and the suffering caused by hyperphagia. The nutritional treatment aims to reduce episodes of binge eating and promote healthy eating habits, improving the patient's relationship with food and his body. Objectives1- Evaluate changes in eating habits, episodes of binge eating and anthropometric data of patients with BED; 2 - To subsidize knowledge to the participant for the construction of food autonomy, consequently improving their quality of life. Method: This study recruited 31 patients diagnosed with BED in S.J Rio Preto and was performed at the clinic of the Nutritionist Tatiana Palotta Minari. The interventions were distributed in 8 individual weekly meetings, based on nutritional educational dynamics, containing games, cooking workshop, sensory food analysis, stretching exercises, relaxation, body self-massage, image / video discussions and applications of 4 questionnaires (Clinical Protocol and Sociodemographic, Body Image Scale - BSQ, Binge Eating Scale - BES, Quality of Life Scale - WHOQOL BREF). Results: Prevalence of female participants, with ages ranging from 35 to 56 years and type C economic class. The analyzes also indicated significant reductions from 1 to 8 weeks in the variables weight, body mass index (BMI), waist circumference, binge eating episodes, BSQ and BES scales. In contrast, there was a significant increase in the quality of life score of the WHOQOL BREF scale. Conclusions: The interventions modulate the anthropometric data, the number of episodes of binge eating and eating habits, consequently improving the quality of life, food autonomy and satisfaction of the patients' body image.